2007
DOI: 10.1007/s12038-007-0074-4
|View full text |Cite
|
Sign up to set email alerts
|

Diet-dependent depletion of queuosine in tRNAs in Caenorhabditis elegans does not lead to a developmental block

Abstract: Queuosine (Q), a hypermodified nucleoside,occurs at the wobble position of transfer RNAs (tRNAs)with GUN anticodons. In eubacteria, absence of Q affects messenger RNA (mRNA) translation and reduces the virulence of certain pathogenic strains. In animal cells,changes in the abundance of Q have been shown to correlate with diverse phenomena including stress tolerance, cell proliferation and tumour growth but the function of Q in animals is poorly understood. Animals are thought to obtain Q (or its analogues) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…This observation is in agreement with earlier studies on various other queuine-deprived eukaryotic species, including Dictyostelium (39), fly (26), and worm (27). It may be concluded that queuine or queuosine-modified (t)RNA does not impact on the development, growth, or reproduction of eukaryotic organisms under laboratory conditions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is in agreement with earlier studies on various other queuine-deprived eukaryotic species, including Dictyostelium (39), fly (26), and worm (27). It may be concluded that queuine or queuosine-modified (t)RNA does not impact on the development, growth, or reproduction of eukaryotic organisms under laboratory conditions.…”
Section: Discussionsupporting
confidence: 92%
“…3) showed that TGT deficiency does not influence viability or sex bias (supplemental Table 1). In addition, breeding of homozygous animals revealed that both males and females have normal fecundity (supplemental Table 2), concurring with the lack of an obvious phenotype in queuine-deficient fly (26), worm (27), and mouse (28).…”
Section: Queuine Deficiency In Hepg2 Cellsmentioning
confidence: 55%
“…A physiological role for Q has eluded discovery partly because of gaps in understanding of the biosynthetic pathway. De novo biosynthesis of Q occurs in bacteria whereas eukaryotes acquire the free base, queuine, from dietary sources (3)(4)(5). The bacterial pathway for biosynthesis of Q has been elucidated up to the penultimate intermediate, epoxyqueuosine (oQ) (6,7).…”
mentioning
confidence: 99%
“…However, contrary to bacteria, eukaryotes lack the enzymatic pathway for queuosine synthesis. Instead, they acquire queuine and queuosine from external sources like nutrition and from the gut microbiota [21,22,23,24] (Figure 1). Q-containing tRNAs from these sources as well as endogenous tRNAs are digested, resulting in queuosine nucleoside, queuosine-3′-monophosphate and free queuine base, which circulates e.g., in blood (serum) and other body fluids (milk, amniotic fluid) and is taken up by the cells [13].…”
Section: Queuosine Modification On Trnasmentioning
confidence: 99%